2010
DOI: 10.1007/s10340-010-0315-4
|View full text |Cite
|
Sign up to set email alerts
|

Activities of digestive and detoxification enzymes in multiple generations of beet armyworm, Spodoptera exigua (Hübner), in response to transgenic Bt cotton

Abstract: To reveal the multi-generation effects of transgenic Bt cotton on the metabolism of secondary target herbivores, the activities of digestive and detoxification enzymes in beet armyworm, Spodoptera exigua (Hübner), fed with transgenic Bt (cv. GK-12) vs. non-Bt cotton (cv. Simian-3) for three successive generations were examined. Significantly lower activities of lipase, carboxylesterase (CarE) and acetylcholinesterase (AChE), and higher activities of trypsin and total superoxide dismutase (T-SOD) were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…Digestive proteases played two critical roles in an insect's physiology: breaking down proteins into amino acids essential for growth and development, and inactivating ingested protein toxins [3032]. Lipases were fundamental to many physiological processes underpinning insect reproduction, development, defense from pathogens and oxidative stress, and pheromone signaling [31,33]. In this study, significantly higher trypsin levels were observed in nymphs grown in elevated CO 2 compared with ambient CO 2 levels, however, there was no significant difference in lipase levels between the two treatments.…”
Section: Nilaparvata Lugens Chemical Composition and Enzyme Activitiesmentioning
confidence: 99%
“…Digestive proteases played two critical roles in an insect's physiology: breaking down proteins into amino acids essential for growth and development, and inactivating ingested protein toxins [3032]. Lipases were fundamental to many physiological processes underpinning insect reproduction, development, defense from pathogens and oxidative stress, and pheromone signaling [31,33]. In this study, significantly higher trypsin levels were observed in nymphs grown in elevated CO 2 compared with ambient CO 2 levels, however, there was no significant difference in lipase levels between the two treatments.…”
Section: Nilaparvata Lugens Chemical Composition and Enzyme Activitiesmentioning
confidence: 99%
“…Trypsin-like serine proteinases were recognized as the main digestive proteinases in the velvetbean caterpillar Xavier et al 2005), as frequently reported in insect species in general and in Lepidoptera in particular (Reeck et al 1999;Terra and Ferreira 2005;Guo et al 2010). Soluble and membrane-bound trypsin-like proteinases were observed and both proved sensitive to natural and synthetic serine-proteinase inhibitors Xavier et al 2005;Pilon et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…The velvetbean caterpillar (Anticarsia gemmatalis (Hübner)) (Lepidoptera: Noctuidae), a key pest of soybean of worldwide importance, is well-adapted to its host proteinase inhibitors (Gallo et al 2001;Oliveira et al 2005;Xavier et al 2005;Fortunato et al 2007). As soybean plants are particularly rich in inhibitors of serine proteinases, the main proteinase reported in Lepidoptera in general and in the velvetbean caterpillar in particular (Reeck et al 1999;Terra and Ferreira 2005;Guo et al 2010), the expression of cysteine proteinases in the midgut of the velvetbean caterpillar is a potential adaptation to circumvent its host defense.…”
Section: Introductionmentioning
confidence: 99%
“…after continuous exposure to insecticides could be associated with the enhanced activities of detoxification enzymes. Measuring multi-generational enzymes activities of the species in response to insecticides can provide proofs of its adaptation to various insecticides (Guo et al 2010). This is essential if maximum efficacy is to be obtained from this already devalued, but still important insecticides group.…”
Section: Discussionmentioning
confidence: 99%